Osmotic Demyelination Syndrome Despite Appropriate Hyponatremia Correction - Jahan, Mansura (Cureus, 2020)
Acute demyelination of the pons or extrapontine areas results in an osmotic demyelination syndrome (ODS), previously referred to as central pontine myelinolysis (CPM) or extra pontine myelinolysis (EPM). It is caused by osmotic dysregulation in the brain. Multiple risk factors have been known to contribute to these osmotic disturbances. Among them, osmotic stress caused by rapid correction of hyponatremia is the most common cause. Other risk factors include liver failure, alcohol dependence, malnutrition, and malignancy. Symptoms can vary depending on the location of the demyelination. It has a high rate of morbidity and mortality. We present a case of ODS in a malnourished patient who was found to have alcoholic hepatitis and invasive colon cancer. The initial presentation was sepsis secondary to pneumonia. The patient was found to be severely hyponatremic at the time of admission, and the hyponatremia was corrected as per the recommendations. The initial non-contrast head computed tomography (CT) scan was unremarkable. However, the hospital course was complicated by a deteriorating neurological exam with encephalopathy despite not overcorrecting the sodium. A short-term follow-up brain magnetic resonance imaging (MRI) eventually revealed ODS. Initially, the findings of ODS were masked due to symptoms of alcohol withdrawal. However, the patient had a quick recovery with the improvement of all the neurological findings.